Improving Detection Rates for Primary Aldosteronism - Libianto, Renata; Stowasser, Michael; Russell, Grant; Fuller, Peter J; Yang, Jun (Experimental and Clinical Endocrinology & Diabetes, 2023)
Primary aldosteronism (PA), once considered a rare disease, is being increasingly recognized as an important cause of hypertension. It is associated with higher rates of cardiovascular complications compared to blood pressure-matched essential hypertension. Targeted treatments are available which can mitigate the excess cardiovascular risks and, in some cases, cure hypertension. Making a timely diagnosis of PA is, therefore, highly beneficial for patients. Furthermore, numerous studies from different parts of the world have found PA to be a relatively common disease that can affect patients in any stage of hypertension, regardless of their age or potassium levels. Despite this well-established data, the current rate of PA detection is appallingly low, much below its actual prevalence. This review explores the challenges that clinicians often face in diagnosing PA and offers strategies that may improve the detection of this potentially curable form of hypertension.
Keywords: Hypertension; Cardiovascular incidences; Cardiovascular risk management; Cardiovascular incidences; Hormones